2020
DOI: 10.1016/j.carrev.2020.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ST-Segment Elevation Myocardial Infarction During COVID-19 Pandemic

Abstract: The number of cases of the coronavirus-induced disease-2019 (COVID-19) continues to increase exponentially worldwide. In this crisis situation, the management of ST-segment elevation myocardial infarction (STEMI) is challenging. In this review, we outline the risks and benefits of primary PCI vs. thrombolysis for STEMI. While thrombolysis may seem like a good choice, many patients have a contraindication and could end up using more resources. Also, with a high probability of the angiogram showing non-obstructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
0
19
1
Order By: Relevance
“…Our study, albeit relatively small, directly compared data regarding patients at a single tertiary care referral center with suspected STEMI at an epicenter during the initial emergence of the current pandemic, to data from the same time period in 2019 before the pandemic demonstrating a similar number of AMI team activations between both periods, increasing by just 3.3% during the pandemic. This is in contrast to previously published data reporting a decrease in the volume of patients presenting with STEMI by as much as 50% [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , 23 ]. None of the studies directly compared data from the same time period before and during the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study, albeit relatively small, directly compared data regarding patients at a single tertiary care referral center with suspected STEMI at an epicenter during the initial emergence of the current pandemic, to data from the same time period in 2019 before the pandemic demonstrating a similar number of AMI team activations between both periods, increasing by just 3.3% during the pandemic. This is in contrast to previously published data reporting a decrease in the volume of patients presenting with STEMI by as much as 50% [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , 23 ]. None of the studies directly compared data from the same time period before and during the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Cardiovascular manifestations of COVID-19 have not yet been fully clarified but early literature has demonstrated that patients with preexisting cardiovascular disease are among the highest risk [ [5] , [6] , [7] , [8] , 13 ]. Furthermore, there has been significant uncertainty of the diagnosis and management of STEMI given the heterogeneity of presentations during the pandemic [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. There is a paucity of STEMI literature directly comparing time periods prior to and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Per guidelines 12 , we trained everyone in the catheterization lab on proper personal-protective-equipment use, designated one laboratory for COVID-19-positive patients or those under investigation, and performed extensive cleaning after each procedure. We also implemented new treatment and risk-stratification algorithms, utilizing non-invasive diagnostic testing such as echocardiogram and cardiac magnetic resonance imaging in patients with low-risk features, ensuring that only high-risk COVID-19 patients with suspected plaque rupture were brought to the catheterization laboratory 25 . Non-invasive imaging allows for the diagnosis of disease processes such as stress-induced cardiomyopathy or pericarditis, which is prevalent in COVID-19 patients, and these patients can avoid going to the catheterization laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study is the first to prove the efficacy of telemedicine use in patients with STEMI during the COVID-19 pandemic. Properly managing the care of patients with STEMI by reducing delay times as much as possible and lessening the adverse impact of COVID-19 is critical and challenging during the pandemic while the number of new COVID-19 cases increases globally and social distancing and quarantines are deemed necessary [ 42 ].…”
Section: Discussionmentioning
confidence: 99%